INPATIENT HEALTH SERVICE SATISFACTION IN SON TAY GENERAL HOSPITAL IN 2022 AND SOME FACTORS ASSOCIATED (Vietnam Journal of Community Medicine, 2024)
Objective: The study aimed to find the satisfaction of inpatients and analyse several factors at SonTay General Hospital.Subject and methods: The Cross-sectional descriptive design was applied using the quantitativemethod. The participants included 388 patients at Son Tay General Hospital. Inpatient health servicesatisfaction was measured by the patient satisfaction scale of Decision No.3869/QĐ- BYT theMinistry of Health in 2019Results: The percentage of inpatient general satisfaction was 96.1%. The mean score of inpatientsatisfaction was 4.06/5. The least satisfying factor was accessibility (3.81 scores). The most satisfyingaspect was staff behavior and professional capabilities (4.3 scores). The need for the medicalexamination for unmarried patients was 3.9 higher than that of married patients. (p< 0.05).Conclusions: The inpatient general health service satisfaction in Son Tay Hospital was high, especiallythe attitude and professional skills of the health staff. The hospital needs more detailed signs/guidanceto improve patient accessibility. This will save time for the patient medical examination and improvepatient satisfaction.
Keywords: Satisfaction, inpatient, Son Tay General Hospital.